"I Want to Be Who I Am": Narratives of Transgender Persons. Issue Volume 11:Issues 3(2017) (3rd July 2017) - Cavanaugh, Gerard; Ladd, Linda
ABSTRACT: Research has documented the difficulties that face persons identifying as transgender, and that research has been steadily increasing. However, the bridge between research findings and practice is often elusive, particularly for those counselors, therapists, and other mental health professionals already in their respective professional lives. This retrospective phenomenological study documented the lives of 16 persons identifying as transgender (11 transwomen, five transmen) as they narrated the difficulties they encountered beginning in childhood through transition in adult life. Eight persons identifying as transgender were younger than age 40 years and eight were older than age 40 years and brought different narratives about their childhood, teen, and adult years.